AutoCAD and its applications advanced, AutoCAD 2000/2000i - Shumaker, Terence M. (Goodheart-Willcox, 2000)
Provides instruction in solid modeling, AutoCAD customization, and other advanced applications. Demonstrates how to use AutoCAD. Serves as a valuable resource once the student begins a career in the drafting industry. DLC: Computer graphics.